1999
DOI: 10.1016/s1074-7613(00)80044-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Successful Immune Response against Hepatitis C Virus

Abstract: To investigate the type of immunity responsible for resolution of hepatitis C virus (HCV) infection, we monitored antibody and intrahepatic cytotoxic T lymphocyte (CTL) responses during acute (<20 weeks) infection in chimpanzees. Two animals who terminated infection made strong CTL but poor antibody responses. In both resolvers, CTL targeted at least six viral regions. In contrast, animals developing chronic hepatitis generated weaker acute CTL responses. Extensive analysis of the fine specificity of the CTL i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
609
0
12

Year Published

2000
2000
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 750 publications
(646 citation statements)
references
References 42 publications
(2 reference statements)
24
609
0
12
Order By: Relevance
“…• Clearance of acute infection in both man and in chimpanzee models is accompanied by strong CD4 + and CD8 + T cell responses against numerous HCV derived antigens [11,[13][14][15][16].…”
Section: Cellular Immunology Of Hcvmentioning
confidence: 99%
“…• Clearance of acute infection in both man and in chimpanzee models is accompanied by strong CD4 + and CD8 + T cell responses against numerous HCV derived antigens [11,[13][14][15][16].…”
Section: Cellular Immunology Of Hcvmentioning
confidence: 99%
“…A broad, vigorous cytotoxic T lymphocyte (CTL) response correlated with viral clearance in a study of six chimpanzees. 3 Similarly, studies in humans have shown that a strong, polyclonal CTL response is associated with viral clearance. 4 It is plausible that the vigor of the immune response is determined, at least in part, by host genetic factors.…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies in humans and in the chimpanzee model indicate that the promptness of both T helper cell and CTL responses after HCV exposure seem to be criti- cal factors in determining the outcome of acute infection, i.e. recovery versus viral persistence [21][22][23][24][25][26][27][28][29][30][31]. Moreover, these data demonstrate that CTL, despite being considerably expanded and expressing a memory effector membrane phenotype (CCR7 -) [30,32,33], are functionally inadequate to fight HCV in a multitude of acutely infected people undergoing a state of long-lasting liver immunopathology [21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%